Analisis Pemasaran Beras di Desa Debowae Kecamatan Waelata Kabupaten Buru Provinsi Maluku - Nur Fitri Utami; Martha Turukay; Ester D. Leatemia (Jurnal Indonesia Sosial Sains, 2022)
The price of rice in the market is influenced by the role of marketing agencies. In this case, the rice marketing process will undergo a long process and will experience price changes from the producer level to the final consumer, resulting in a rice price gap between producers and consumers. This makes the rice marketing aspect an important activity in determining farmers' income. The purpose of this study is to determine marketing channels, margins, and marketing efficiency. The population in this study were 762 lowland rice farmers. Determination of the sample using the slovin method, so that the selected respondents were 42 farmers. The determination of the merchant respondents was carried out by tracing (tracing sampling). The sample of the respondents was 10 traders, namely 6 grinders, 2 large collectors, and 2 retailers. The analytical tools used are descriptive analysis, marketing margin analysis, and marketing efficiency analysis. The results showed that there were 5 patterns of rice marketing channels in Debowae Village, namely: farmers-grinders-consumers, farmers-grinders-retailers-consumers, farmers-grinders-large collectors-consumers, farmers-grinders-big collectors-retailers-consumers, and farmers-big collectors-retailers-consumers. The highest total marketing margin is in marketing channel II, which is IDR. 2,000/kg, while the lowest total margin is in marketing channel I, which is IDR.467/kg. The most efficient marketing channel is channel I with the smallest efficiency value of 3.35 percent.